Strength Analysis for Surface-mounted Permanent Magnet Rotor in High-Speed Motor - Liangliang Chen; Changsheng Zhu (Indonesian Journal of Electrical Engineering and Computer Science, 2014)
In the surface-mounted high-speed permanent magnet motor, the magnets are not mechanically strong enough to bear the centrifugal stress resulted from the high speed rotating, thus a sleeve composed of the carbon-fiber bandage is usually employed to retain the permanent magnets on the rotor surface. According to the surface-mounted high-speed permanent magnet rotor retained by a carbon-fiber bandage, in this paper, an analytical model for calculating rotor strength was presented based on the theory of elastic mechanics. Then the results of analytical model were compared with the calculations of finite-element method. It was shown that the analytical model proposed in this paper could accurately predict the stress distribution of the surface-mounted high-speed permanent magnet rotor fixed by a carbon-fiber bandage. Finally, the influence of the bandage thickness and shrink range between the permanent magnets and the bandage on rotor stress was investigated based on this analytical model of rotor strength.